Methodological recommendations for the evaluation of freight forwarding services - D. R. Abdyusheva (Вестник университета)
Individualization of service is the most reasonable way to implement a customeroriented approach in freight forwarding services in conditions of intense competition. The article considers the structure and content of the main mathematical methods for assessing consumer loyalty. The necessity of developing an indicator of service individualization and its systematic use in the practice of organizations` activities for the growth of competitiveness is actualized. The conditions of application of the service individualization method in practice are studied. The systematic use of this indicator will allow an organization in the field of freight forwarding services to form partnerships with customers, increase their satisfaction and loyalty, and ensure a sustainable nature of interaction with customers in the long term. In this regard, the assessment of client performance indicators is the basis for the development of an organization’s strategy.